EXPLORING THE EFFECTS OF ROLE AMBIGUITY AND JOB SATISFACTION ON WORKPLACE CREATIVITY - Wahyudi, Agus; Januarista, Januarista; Muliati, Lisdewi (Universitas Muhammadiyah Tangerang, 2025)
This study examines the influence of role ambiguity and job satisfaction on employee creativity in a public sector organization, where bureaucratic structures often hinder innovative behavior. The research aims to understand how psychological and environmental factors shape creativity among revenue management officers at UPTD Pengelolaan Pendapatan Daerah Balaraja, Banten. Using a quantitative explanatory approach, data were collected from 64 employees via questionnaires and analyzed using multiple regression with SPSS. Results indicate that role ambiguity negatively affects creativity, while job satisfaction has a significant positive impact. Collectively, both variables significantly influence employee creativity, explaining a substantial portion of its variance. The study contributes to public sector management literature by highlighting the dual role of job design and affective states in fostering innovation. Its novelty lies in exploring creativity determinants in a local government revenue unit—an under-researched context in organizational studies. Findings offer practical guidance for improving work design and motivation to enhance innovation in public service environments.